Generated Voltage Control In A Switched Reluctance Motor/generator - Wohlgemuth Fleury Veloso da Silveira, Augusto; Alves de Andrade, Darizon; Fleury Veloso da Silveira, Augusto; Coutinho Gomes, Luciano; Augusto Bissochi Jr., Carlos; de Paula, Hélder (Eletrônica de Potência, 2010)
This paper reports on the switched reluctance machine operating as motor/generator (SRM/G) excited through an external power source. The half-bridge static converter topology is used to drive the machine in either modes of operation. Transition from motor to generator mode is firstly discussed and results from both simulation and experimental tests are included. Operating as generator, the output generated voltage is a function of the phase magnetization level during excitation; therefore, by controlling the phase excitation level, the output voltage is also controlled. Three output voltage control techniques are proposed and analyzed: 1- Variable Angle (VA), effected by controlling the phases turning off angles with a fixed DC link excitation voltage; 2 - Chopping (CH), attained by chopping the DC link supply during the phases magnetization while keeping a fixed conduction period; and 3 – Variable Link (VL), reached by controlling the DC link excitation voltage by means of a DC-DC buck converter in a fixed conduction period. For the experimental work, full digital control is implemented. Results obtained with the implementation of the output voltage control techniques are presented. Relative performance comparison is included, showing that the CH followed by VL strategy brings the best outcome.